RELATIONSHIP BETWEEN SUSTAINABILITY INDEX AND THE FINANCIAL-ECONOMIC INDICATOR OF THE BRAZILIAN ENERGY COMPANIES - Fasolin, Luiza Betânia; Kaveski, Itzhak David Simão; Chiarello, Tânia Cristina; Marassi, Rodrigo Barraco; Heinn, Nelson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Society is increasingly demanding that organizations consider the economic, social and environmental issues into their activities. With this, the information that involve sustainability practices gain importance. This study refers to the sustainability practices of companies generating and distributing energy in Brazil that are listed on the BM&FBovespa and has as objective to verify the influence between the sustainability index and the financial and economic indicators of energy companies listed on the BM&FBovespa. The sample consists of 31 companies that sent their sustainability reports in 2010 to Aneel. The methodology used was descriptive quantitative method, using the technical documentation, and multiple linear regression using the statistical software IBM ® SPSS ® version 21. For data collection, a checklist has been prepared to highlight the environmental, social and economic disclosed by companies. But it was also used Economática for economic-financial variables. The results show that the financial and economic indicators of size, profitability and indebtedness of generating and distributing electricity Brazilian did not influence the level of disclosure of sustainability practices of these companies.